The Study of Risk Disclosure in the Case of Thai Listed Companies - Kongprajya, Chalida (2010)
In this age of globalization, firms are automatically put into a more vulnerable position to risks. This affects both business operation of the firms and decision making process of stakeholders. Therefore, risk management and risk reporting is gaining more interest from business, as well as academic community. In this paper, a developing Asian country, Thailand, is selected as a country of focus. The study composed of two parts. The first part is a review of accounting standards development and actual reporting practices in Thailand and other selected countries. It is found that standard development of Thailand, like other Asian countries, tends to follow the trend of international standard setting. Since Thailand is trying to gain its place in the world competition level, it may hardly be develop its own set of reporting standards regardless of international trend. The part of empirical study then proceeds in performing content analysis on the sample of 30 annual reports of Thai listed companies. It is found that company size and level of company’s risk potentially affect volume of risk disclosures in a positive ways. Firms in financial industry also seem to disclose more risk information than non-financial firms. Empirical result further uncovers specific areas on Thai risk reporting that improvement is needed, which are neutrality of disclosures, i.e., readers may need more specific disclosures that can inform them about potentiality in good or bad state of the event. More disclosures on future risks also likely enhance decision making of stakeholders. Existing level of monetary risks and financial risks is comparatively low. The tone of risks are found to be mostly positive, confirming the attribution theory that directors normally make disclose good news more than bad news.